Analysis of factors associated with IVF/ICSI clinical outcomes in advanced maternal age patients with normal ovarian reserve under the POSEIDON criteria - Meng, Yicen; Zhang, Qianjie; Song, Yixuan; Liu, Qian; Li, Wei; Yang, Jing; Li, Saijiao (Frontiers in Endocrinology, 2025)
BackgroundThere is limited research about the pregnancy outcomes of POSEIDON group 2 patients. This study aims to evaluate the factors related to the clinical outcomes of in vitro fertilization (IVF) and/or intracytoplasmic sperm injection (ICSI) in POSEIDON group 2 patients, so as to provide clinical guidance to improve clinical outcomes.MethodsA total of 1,249 IVF/ICSI cycles of POSEIDON group 2 patients were retrospectively analyzed from July 2019 to September 2024. The patients were divided into different groups according to live birth, maternal age, and endometrial thickness (EMT). The clinical outcomes were compared between groups.ResultsCompared with the non-live birth group, maternal age, gonadotropin (Gn) dosage, and Gn total dosage were significantly lower, while EMT was significantly higher in the live birth group (p < 0.05). The type of infertility showed statistically significant differences (p = 0.013). Multivariate logistic regression analysis indicated that maternal age (OR = 1.195, 95% CI: 1.077–1.327; p = 0.001) and EMT on transfer day (OR = 0.887, 95% CI: 0.820–0.959; p = 0.003) were independent influencing factors for live birth in POSEIDON group 2 patients. According to the receiver operating characteristic (ROC) curve predictive cutoff value, the patients were divided into group A (age < 38 years, n = 249) and group B (age ≥ 38 years, n = 155). Group A had a higher human chorionic gonadotropin (hCG)-positive rate (55.8% vs. 34.2%, p < 0.001), embryo implantation rate (35.2% vs. 19.2%, p < 0.001), clinical pregnancy rate (47.8% vs. 29.7%, p < 0.001), and live birth rate (37.3% vs. 20.0%, p < 0.001) and a lower early miscarriage rate (12.6% vs. 28.3%, p = 0.016) than group B. According to the ROC predictive cutoff value of EMT, group A patients were further divided into group A1 (EMT < 11.65 mm, n = 136) and group A2 (EMT ≥ 11.65 mm, n = 113). Group B patients were divided into group B1 (EMT < 11.65 mm, n = 93) and group B2 (EMT ≥ 11.65 mm, n = 62). Compared with group A1 and group A2, group B1 had a lower hCG-positive rate (28.0% vs. 49.3%, p = 0.001; 28.0% vs. 63.7%, p < 0.001), embryo implantation rate (14.7% vs. 32.2%, p < 0.001; 14.7% vs. 40.2%, p < 0.001), clinical pregnancy rate (23.7% vs. 41.2%, p = 0.006; 23.7% vs. 55.8%, p < 0.001), and live birth rate (16.1% vs. 33.8%, p = 0.003; 16.1% vs. 41.6%, p < 0.001).ConclusionsMaternal age and EMT on transfer day are independent factors affecting IVF/ICSI clinical outcomes in POSEIDON group 2 patients. Among these, maternal age <38 years or EMT ≥ 11.65 mm indicated better clinical outcomes. Further stratification by age and EMT on transfer day may optimize clinical outcomes in POSEIDON group 2 patients.